VD_FINDINFO HC / 2016 / 113 vom 22. Januar 2016 - VD Tribunal cantonal (2016)
FRAIS JUDICIAIRES, DÉPENS, DÉCISION DE RENVOI, LOI SUR LE TRIBUNAL FÉDÉRAL | 92 CPC, 68 al. 5 LTF, 106 al. 1 CPC (CH), 404 al. 1 CPC (CH), 95 CPC (CH)